Responsive supramolecular prodrug nanoparticles for cancer therapy - Chen, Hongzhong (2017)
Prodrugs are modified drugs which can be converted to the original form after uptake by tumor or activation by external stimuli. Advantages of prodrugs include better water solubility, higher selectivity, longer circulation time, and controlled release than the free anticancer drugs. Common prodrugs still have an obvious drawback that is low drug content due to inherent balance between the hydrophobic part with the hydrophilic part. Therefore, construction of prodrugs using small molecules with high drug loading percentage and inherent amphiphilic property has attracted a lot of attention. To obtain better therapeutic performance, a lot of external stimuli strategies have been introduced to achieve on-demand drug release during the design of prodrugs. Benefiting from the host-guest chemistry, supramolecular amphiphiles show numerous advantages, because fabrication was achieved by the means of various non-covalent interactions. Supramolecular amphiphilies are constructed by two parts with various noncovalent interactions, which efficiently simplify the tedious covalent synthesis and functional modification of the traditional amphiphiles. Owing to the advantages mentioned above, supramolecular amphiphiles have garnered tremendous interest of the researchers, especially in biomedical relevant fields. Gene therapy has gained considerable attention in the past decades, due to its promising therapeutic application in genetic diseases, cancer, cardiovascular and infectious diseases. However, due to its rapid degradation by serum nucleases in the blood, there are still on-going efforts to develop effective carrier vectors.